Drug-induced hypersensitivity reaction presenting as systemic capillary leak-like syndrome with polyserositis: a case report - Ninh Xuan Nguyen; Ngoc Tien Pham; Huong Thi Thanh Le; Quoc Viet Tran; Hang Ngoc Thuy Tran; An Thien Do (BMC Rheumatology)
Abstract Background Systemic capillary leak syndrome (SCLS) is a rare disorder characterized by increased vascular permeability leading to third-spacing of fluids and protein. Drug-induced hypersensitivity reactions can mimic SCLS clinically and radiologically. Case presentation A 42-year-old Vietnamese man developed abdominal distension, facial edema, and dyspnea after initiation of Helicobacter pylori eradication therapy. Imaging revealed pleural, pericardial, and peritoneal effusions, periportal edema, and interstitial pulmonary edema. Laboratory results showed hyponatremia, hypoalbuminemia, and mild anemia. Autoimmune screening revealed ANA positivity (1:80, speckled) and lupus anticoagulant, though extractable nuclear antigens were negative. The patient improved rapidly with corticosteroids and antihistamines. Conclusion This case suggests a probable drug-induced systemic hypersensitivity reaction mimicking capillary leak syndrome, occurring in a patient with latent immune dysregulation. Awareness of this presentation may facilitate early recognition and appropriate immunomodulatory treatment while avoiding unnecessary interventions.